Analysis of Healthcare-Associated Infections in COVID-19 patients admitted to an Intensive Care Unit (Research, Society and Development, 2023)
Introduction: Healthcare-associated infections (HAIs) are a major public health problem. Objective: To evaluate the profile of SAIs in patients with COVID-19 admitted to the intensive care unit (ICU) in a public hospital in southern Brazil. Method: Cross-sectional, retrospective study, conducted between March 2020 to October 2021, of patients with COVID-19 hospitalized in ICU with IRAS. Results: The main infection was ventilator-associated pneumonia (230 cases), followed by urinary tract infections (160 cases) and bloodstream infections (103 cases), associated with the presence of catheter. Regarding the main microorganisms, the high prevalence of multidrug-resistant Acinetobacter baumannii (112 cases) was noteworthy in ventilator-associated pneumonia, with an increasing increase in the analyzed period. The expressiveness of fungal infections, especially Candida albicans, was evidenced. Patients with ventilator-associated pneumonia had lower mortality rates (OR= 0.31; p= 0.034), which increased significantly with increasing days of ICU stay (OR= 3.02; p= 0.0000007). The profile of the patients was mainly male, with significant use of antimicrobials and antifungals, high degree of pulmonary impairment, with evolution to death. Among the predictors of mortality, the most impacting was acute renal failure (OR= 4.45; p=0.0002) and the least related was pulmonary thromboembolism (OR=0.47; p= 0.0167).  Conclusion: The high percentage of bacterial and fungal IRAS was evidenced. The highest mortality predictor was acute renal failure, while the lowest mortality was pulmonary thromboembolism.